Evaluation of interventions focused on reducing propeller scarring by recreational boaters in Florida, USA. (15th March 2020) - Barry, Savanna C.; Raskin, Karissa N.; Hazell, Joy E.; Morera, Maria C.; Monaghan, Paul F.
Abstract: Propeller scarring by recreational vessels is a known threat to seagrass meadows in Florida. Despite decades of awareness about the problem, there has been little meaningful progress in addressing this largely preventable stressor. We consider it preventable because it rests on human behaviors, which can be changed by education, technology, social norms, and policy. However, past attempts to address seagrass scarring have rarely been evaluated for effectiveness. Thus, very little guidance exists for natural resource managers, educators, and policy makers responsible for allocating limited resources toward effective interventions. Using a social marketing approach, we deployed two separate interventions, one education-based and the other cue-based (navigational aids) in Florida, USA. We measured boater behavior and attitudes before and after the interventions to assess the relative effectiveness of each. Navigational aids elicited a clear behavioral improvement across a broad cross-section of boaters, while minimal effects were observed for the educational intervention. However, analyses suggest the recreational boating audience can be segmented by factors such as experience level to better target educational messages in future seagrass protection efforts. These results will assist seagrass managers, educators, advocates, policy makers, and boating industry stakeholders in deploying an efficient combination of approaches to better address propeller scarring in Florida's seagrass meadows. Graphical abstract: Image 1 Highlights: Navigational aids produced a clear short-term behavioral response from boaters. More experienced boaters viewed seagrass scarring as a more serious issue. New boaters who saw educational materials exhibited the most concern about scarring. Audience segmentation can be applied to reach boaters with appropriate interventions.